Response of Vitis vinifera L. cv. Pinotage to Irrigation Strategy and Trellis System in the Breede River Valley Region: Vegetative Growth, Yield and Juice Characteristics - Howell, C.L.; Myburgh, P. A. (South African Journal of Enology and Viticulture, 2024)
Pinotage is a South African bred red wine cultivar and is second only to Shiraz in terms of the country’s wine exports. Since rainfall in the Breede River region is low, vineyards in this region depend on irrigation. The sensitivity of Pinotage/99R to water deficits and the most suitable irrigation strategy during water restrictions were studied in a field trial from 1998/99 until 2000/01. The possibility to produce more grapes with the same volume of irrigation water was also investigated. Irrigation strategies entailed combinations of 50% readily available water (RAW) depletion, 75% RAW depletion and no irrigation between various phenological stages, viz. budbreak, flowering, pea size berries, véraison, 17°B and harvest. Irrigation applied at 50% RAW depletion from budbreak in September until harvest in February was regarded as the control. Each experiment plot was split into a six-strand vertical hedge and a two-tier vertical trellis. The experiment layout was a split plot, randomised block design. Cane mass of grapevines on the two-tier trellis was lower compared to those on the six-strand hedge. Irrigation at 75% RAW depletion level until harvest tended to reduce cane mass compared to more frequent irrigation. Drier soil conditions reduced berry mass, regardless of the trellis system. Sustained water deficits reduced yield, but had little effect on juice acidity and pH. More Pinotage grapes were produced on the two-tier vertical trellis compared to the six-strand hedge with the same amount of irrigation, thereby reducing the blue water footprint and increasing the irrigation water use efficiency substantially.